EXPLORING THE BEST WAYS TO SUPPORT FIRST YEAR UNIVERSITY STUDENTS’ ACADEMIC WRITING SKILLS - Perez del Aguila, Rossana (2014)
This article presents the findings of an action research project carried out in 2012 with 12 first-year university students taking ‘Education Studies’ in a university in England. The aim of the project was to explore the best ways to support students’ academic writing skills. The literature review highlights the challenges students encounter when trying to learn the discourse of adiscipline; and in the light of this examination, a reflection on the strengths and weaknesses of my own practice provides the context for carrying out an action research project. The teaching intervention was assessed using the following methods of data collection: questionnaires and semi-structured interviews with students, and content analysis of my own feedback on student’s final assignments. The outcomes of the research demonstrate that students’ difficulties with their academic writing are related to their struggle to understand specialized concepts, theories and methods of the discipline.